Enhancing nitrogen management in corn silage: insights from field-level nutrient use indicators - Olivo, Agustin J.; Workman, Kirsten; Ketterings, Quirine M. (Frontiers in Sustainable Food Systems, 2024)
Corn (Zea mays L.) silage is an important feed ingredient in dairy cow diets in New York (NY). Improving corn nitrogen (N) management will help increase farm profitability while reducing environmental impacts from N losses. The objectives of this study were to (1) characterize field-based N balances and other N use indicators for corn silage, and (2) describe major contributors to high balances and inefficiencies as a first step to understand potential opportunities to improve N management. Field-level N balances (N supply – N uptake) and associated N use indicators were derived for 994 field observations across eight NY dairy farms and five years. Available and total N balances per ha, which differed only in the fraction of manure N accounted for (plant-available N or total N, respectively), yield-scaled N balances, and N uptake/N supply were calculated. The median balance across all fields was 111 kg N ha-1 for available N and 245 kg N ha-1 for total N. Median yield-scaled available and total N balances were 2.7 and 6.0 kg N Mg-1, respectively. Median N uptake/N supply was 0.60 for available N and 0.41 for total N. Differences in N use indicators were larger among farms than among years within a farm. The amount of N supply greatly influenced N use indicators, manure N supply explaining the largest portion of the variability. At the whole-farm level, balances per ha were positively related to farm’s animal density and impacted by farm crop rotations and within-farm allocation of manure N. We conclude that farms have opportunities to improve upon N management for corn by adjusting N supply based on realistically attainable yield, fully crediting manure and sod N contributions, improving manure inorganic N utilization efficiency, optimizing animal density, and/or exporting manure. Future work is needed to identify feasible ranges for field-level N balances and incentivize the implementation of this assessment through adaptive nutrient management policies.